Similarity in qPCR Assay Parameters Validates the Reliability of Two Microtube Brands - Avila, Lucas dos Santos; da Silva Vaz Junior, Itabajara; Waldman, Jéssica (Acta Scientiae Veterinariae, 2025)
Background: Quantitative PCR (qPCR) is a powerful molecular biology technique widely used for gene transcription analysis, pathogen detection, food and environmental contamination monitoring, due to its high sensitivity, specificity and accuracy when compared to immunological and microbiological assays. It enables real-time monitoring of DNA amplification playing a critical role in medical diagnostics, vaccine development and cancer research. This makes qPCR an essential technique in agriculture, forensics and environmental monitoring, solidifying its position as one of the most versatile tools in modern science. However, the cost of this molecular method remains a significant limitation, as expenses related to equipment and consumables (such as pipette tips, enzymes and reaction tubes) make the technique relatively expensive, particularly for high-throughput applications or laboratories with limited budgets. Materials, Methods & Results: The experiments were conducted using 2 very well characterized constitutive genes from Rhipicephalus microplus, 40s ribosomal protein and cyclophilin A, allowing a consistent and reliable analysis of qPCR assay performance. These genes were selected due to their stable transcription across different biological conditions, ensuring minimal variability in amplification efficiency. Statistical analysis was performed using Mann-Whitney test, based on the mean and standard deviation of the Ct values, with a significance threshold set at P < 0.01. No significant difference (P = 0.99) was observed between the microtubes evaluated in this assay, indicating that, despite being from different manufacturers and price categories, the tubes presented comparable performance, in terms of amplification efficiency and reproducibility. This consistency was observed even when testing different reference genes and biological samples, further validating the robustness of the findings. Notable, the most cost-effective microtube, evaluated in this work, offered over 70% savings compared to the alternative, making it a highly attractive option for laboratories seeking to reduce expenses without sacrificing data quality. Discussion: Various alternatives have been explored to reduce the cost of the qPCR assay while maintaining reliability. These include the use of more economical thermal cyclers, minimizing consumable wastes, adopting portable qPCR system, simplifying nucleic acid extraction protocols, and optimizing reaction conditions to reduce the impact of nhibitors. Among consumables, approaches such as the reuse of pipette tips (where feasible) and reducing the volume of each reagent in the reactions have been reported. However, studies systematically evaluating the performance of different microtube brands in qPCR applications remain scarce. Here, 2 microtubes with identical physical specifications, but differing in brands and values, were tested in qPCR assays using constitutive tick genes. The results demonstrated no significant differences in reaction efficiency or reproducibility between the tubes, confirming that cost-saving alternatives can be implemented without affecting experimental outcomes. Therefore, the lower-cost microtube represents a viable and practical alternative to reduce expenses in qPCR assays while maintaining high performance standards. Future studies could expand this evaluation to include additional brands, tube materials, and reaction conditions to further validate these findings and optimize cost-efficiency in molecular biology workflows. Keywords: qPCR; microtubes; performance, molecular assay, tick, cost-efficiency.